1991
DOI: 10.1002/aqc.3270010104
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of freshwater fish in the British Isles: The current status and biology of threatened species

Abstract: 1. The objective of this paper is to review the status of all freshwater fishes in the British Isles and to identify theatened species, races and communities which are in need of conservation.2. Using objective criteria to assess the degree of threat, two of the 55 freshwater species known in the British Isles are thought to be extinct here and eight are believed to be under significant threat.3. The biology of these ten species is reviewed. They are: Sturgeon Acipenser sturio, Allis Shad Alosa alosa, Twaite S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 33 publications
0
57
0
1
Order By: Relevance
“…Schulz et al [27] based on the nucleotide sequence of a short D-loop segment (328 bp) in Coregonidae, identified as many as 10 haplotypes. Reed et al [46] by analysing the complete D-loop, reported 4 length variants resulting from duplication of single D-loop segments in the investigated Coregonus species, but also demonstrated a high variability of this region resulting from nucleotide substitutions and indel mutations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Schulz et al [27] based on the nucleotide sequence of a short D-loop segment (328 bp) in Coregonidae, identified as many as 10 haplotypes. Reed et al [46] by analysing the complete D-loop, reported 4 length variants resulting from duplication of single D-loop segments in the investigated Coregonus species, but also demonstrated a high variability of this region resulting from nucleotide substitutions and indel mutations.…”
Section: Discussionmentioning
confidence: 98%
“…The European cisco is a valuable species, for many years covered by programmes of renewal and reintroduction, e.g., in Poland, Scotland, England and Germany [46][47][48]. This is necessary, as the natural populations are reduced due to the deteriorating quality of water and currently constitute a small fraction of the total population [10].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty seven of the 55 freshwater fish species on the British list are found in NNRs. The majority of the fish found, however, are those most common in Great Britain and only three of the 10 species under greatest threat (Maitland and Lyle, 1991) occur in NNRs.…”
Section: National Nature Reservesmentioning
confidence: 99%
“…Of these, nine are category E species (seven of which have been introduced to this country and are therefore of questionable conservation concern -see Maitland and Lyle, 1991a) one is in category D (Spined Loach) and one is category I (Sturgeon). None of the three category A species -Allis Shad, Twaite Shad and Vendace -occurs in NNRs.…”
Section: -7mentioning
confidence: 99%